PERAN TOKOH AGAMA DALAM MEMBINA AKHLAK REMAJA DI KELURAHAN TALANG BENIH CURUP - Nurjannah; Tryanti Nur Aprida; Ayu Selpiana; Amalia Serena; Cindi Ameliya (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Religious figures are people who carry out da'wah, both verbally and in writing, or do good deeds individually and in groups. Religious figures play a very important role in inviting teenagers to take part in da'wah activities. Teenagers will get used to praying, listening to religious lectures, and carrying out other religious activities which will have a positive influence on the teenagers themselves. In Talang Benih Curup Village, it is known that the number of teenagers in Talang Benih Curup Village is 3,523 boys, 3,475 girls. Where the morals of teenagers are generally quite good, but there are some teenagers who have less good morals, such as doing glue. This research aims to find out the role of religious figures in developing morals among teenagers in Talang Benih Curup Village, as well as what obstacles are faced by religious figures in carrying out da'wah activities in Talang Benih Curup Village. The research method uses qualitative descriptive research. This research uses two data sources, namely primary data and secondary data. In collecting research data using interview, observation and documentation methods so that the data obtained is reduced and then analyzed and conclusions drawn. The results of the research show that the role of religious figures in fostering the morals of teenagers in Talang Benih Curup Village is by first forming a forum for da'wah activities such as the Al-Qur'an Education Park (TPA), forming the Youth Islamic Mosque (RISMA) and the Taklim Council. Second, carrying out da'wah activities in the form of recitations, morning lectures, and commemoration of Islamic holidays (PHBI), and third is providing da'wah material about morals, in addition to the material faced by Religious Figures in carrying out da'wah activities, namely the busyness of Religious Figures who also act as civil servants. (PNS) or other jobs, lack of cooperation from parents, lack of motivation from teenagers themselves to take part in da'wah activities, as well as the influence of technological developments, especially the internet. And the solution in developing adolescent morals is to form good youth cadres, Mosques and Langgars must be driven by the younger generation and the role of parents in providing good examples and motivation to teenagers in participating in da'wah activities.